On Adam Mickiewicz's theory of romanticism - Novruzov, Rafig (Abdul Media Literasi, 2025)
This article is devoted to considering the views of the famous Polish classic Adam Mickiewicz on oriental romanticism. It is known that the Polish poet is considered the founder of Polish romanticism. At the same time, the beginning of this trend in Mickiewicz's poetry was laid by sonnets on eastern themes, which later found continuation in other forms of creativity. The creation of the West-Eastern synthesis was not accidental for his work. The fact is that even before the appearance of the cycle of poems on eastern motives, Mickiewicz wrote two unique articles (